Pretreatment expectations and posttreatment satisfaction with different prosthodontic treatments in a Saudi population - Ahmed Yaseen Alqutaibi; Abdullah Faisal Alharbi; Abdullah Mohammed Alharbi; Ghofran Ali Karbouji; Emad Yahya Dagharire; Afaf Aboalrejal (Wolters Kluwer Medknow Publications, 2022)
Introduction: The dentist-patient relationship and the patient's expectation before prosthodontic treatment are significant in achieving patients' satisfaction. There are not enough studies in the Saudi population on how the expectation can affect patients' satisfaction for patients rehabilitated with different prosthetic options. Aim: This study aimed to investigate the effect of gender, prosthesis type, and patients' expectations of different prosthetic treatments on the patient's satisfaction. Materials and Methods: Data were collected at the dental hospital, Faculty of Dentistry, Taibah University. A total of 125 participants evaluated their expectations of and satisfaction with different prostheses types regarding esthetics, chewing, comfort, and phonetics, also assessed their perception of the dentists' conduct by using a Visual Analog Scale. Results and Discussion: The study included 125 participants (50.4% females, 49.6% males), with a mean age of 39.76 ± 15.42. Regarding the prosthesis type, there were no statistically significant differences between expectations and satisfaction in all domains except with chewing with a fixed denture prosthesis, in which satisfaction exceeded expectations with a statistically significant difference (P < 0.05). Most participants scored their perception of the dentist's conduct above average and described their dentists as professional, very concerned, and careful. Female participants recorded statistically insignificantly lower expectations and satisfaction scores than males regarding esthetics, comfort, and phonetics with all prosthesis types (P > 0.05). Conclusion: The study's findings suggested that satisfaction levels were correlated with prosthesis type, pretreatment expectations, and the gender of the treated patients.